2014
DOI: 10.1080/23302674.2014.951714
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating a supply chain with backup supplier through buyback contract under supply disruption and uncertain demand

Abstract: This paper develops a supply chain model consisting of a single supplier and a single retailer. The market demand is assumed to be stochastic and the supplier is prone to disruption. The centralised model is provided as benchmark, and non-coordinated model is studied with the wholesale price-only contract. To enhance the total expected profit, we apply buyback contract and show that the chain may be coordinated thorough this contract, although the chain is vulnerable to disruption. To mitigate the effect of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Mavrotas et al 2008;Xidonas and Psarras 2009;Xidonas et al 2009aXidonas et al , b, 2010aSteuer et al 2005Steuer et al , 2006aSteuer et al , b, 2007aZopounidis and Doumpos 2002;Zopounidis 1999;Hurson and Zopounidis 1993, 1995, 1997Spronk and Hallerbach 1997;Zeleny 1977Zeleny , 1981Zeleny , 1982Colson andZeleny 1979, 1980). For deep reviews of other solution methods, consider the below references: Awasthi and Omrani (2019), Duan et al (2018), Dubey et al (2015), Gharaei et al (2019a, b, c), Giri and Bardhan (2014), Giri and Masanta (2018), Hao et al (2018), Kazemi et al (2018), Rabbani et al (2019Rabbani et al ( , 2020, Sarkar and Giri (2018), Sayyadi and Awasthi (2018a, b), Shah et al (2020). Shakarabi et al (2019), Tsao (2015) and Yin et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mavrotas et al 2008;Xidonas and Psarras 2009;Xidonas et al 2009aXidonas et al , b, 2010aSteuer et al 2005Steuer et al , 2006aSteuer et al , b, 2007aZopounidis and Doumpos 2002;Zopounidis 1999;Hurson and Zopounidis 1993, 1995, 1997Spronk and Hallerbach 1997;Zeleny 1977Zeleny , 1981Zeleny , 1982Colson andZeleny 1979, 1980). For deep reviews of other solution methods, consider the below references: Awasthi and Omrani (2019), Duan et al (2018), Dubey et al (2015), Gharaei et al (2019a, b, c), Giri and Bardhan (2014), Giri and Masanta (2018), Hao et al (2018), Kazemi et al (2018), Rabbani et al (2019Rabbani et al ( , 2020, Sarkar and Giri (2018), Sayyadi and Awasthi (2018a, b), Shah et al (2020). Shakarabi et al (2019), Tsao (2015) and Yin et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [33] considered both the production competition between partially substitutable products made by different manufacturers, and the competition between retail stores, and they found that as consumers' environmental awareness increases, retailers and manufacturers with superior ecofriendly operations will benefit [33][34][35][36]. Ghosh and Shah [37] studied supply chain coordination issues arising out of green supply chain initiatives and explored the impact of cost sharing contract on the key decisions of supply chain players undertaking green initiatives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the bottled drinking firm is immense, complex, and affected by the monetary, community, and fiscal concerns. The drinking water industries must prioritize managing market dynamics to diminish the instability supply chain from the downstream and upstream (Giri & Bardhan, 2014). Its industry adopts supply chain strategies that are lean strategy and agile strategy.…”
Section: Introductionmentioning
confidence: 99%